Successful Management of Bilateral Subdural Hematoma: Combining Bilateral Middle Meningeal Arteries Embolization and Unilateral Burr Hole Craniostomy—A Case Report - Soetanto, Gameliel Wibowo; Lilikwatil, Pieter Melchias Jacob; Usman, Fritz Sumantri (AKSONA, 2025)
Highlight: The approach to bilateral SDH management was still tailor-made, especially in the elderly, due to the benefit of reducing intracranial pressure and the risk of increased complications and recurrent bleeding. In cases of bilateral SDH, middle meningeal artery (MMA) embolization before surgery may increase the favorable outcome and lower the risk of SDH rebleeding.   ABSTRACT Introduction: Subdural hematoma (SDH) is frequently seen in the elderly population. Although anticoagulant use and traumatic brain injury are recognized risk factors, the exact cause of subdural hematomas in certain cases remains unknown. Furthermore, unilateral or bilateral hemispheres may be involved in SDH, which can occur acutely or gradually. The old age group’s SDH profile, which includes several comorbidities, may complacte surgery, the gold standard for treatment. Embolization of the middle meningeal artery (MMA) may be a treatment option because it is safer and has a higher success rate in terms of improvement compared to complications. It can be done as either a standalone procedure or an adjuvant to surgery. Case: An elderly male patient experienced acute left-sided weakness that worsened over three days. Imaging revealed bilateral SDH, with symptomatic chronic SDH on the right side, asymptomatic acute SDH on the left side, and midline shift. Bilateral MMA embolization was done, followed by burr hole craniostomy, which resulted in clinical and radiological improvement throughout a three-month post-intervention period. Conclusion:MMA embolization can improve clinical outcomes and prevent recurrent bleeding, which makes it a potential treatment option for severe symptomatic SDH, especially in patients with comorbidities.